Synergistic influence of cytokine gene polymorphisms over the risk of dementia: A multifactor dimensionality reduction analysis - Juárez-Cedillo, Teresa; Martínez-Rodríguez, Nancy; Vargas-Alarcon, Gilberto; Juárez-Cedillo, Enrique; Valle-Medina, Antonio; Garrido-Acosta, Osvaldo; Ramirez, Alfredo (Frontiers in Aging Neuroscience, 2022)
Abstract Evidence supports the important role of neuroinflammation in some types of dementias. The aim of this study was to evaluate the effect of epistasis of genes cytokines such as interleukin IL-α, IL-6, tumor necrosis factor (TNFα) and interferon gamma (IFN-γ) on the susceptibility to the development of dementia. Materials and methods: 201 patients diagnosed with dementia and 534 controls were include in the study. The Multifactor-Dimensionality Reduction (MDR) analysis was performed to identify the epistasis between SNP located in genes of IL-α (rs1800587), IL-6 (rs1800796), and TNFα (rs361525, rs1800629) IFNγ (rs2069705). The best risk prediction model was identify based on precision and cross-validation consistency. Results: Results: MDR analysis detected a significant model with the genes TNFα, IFNγ, IL1α and, IL6 (prediction success 72%, p<0.0001). When risk factors were analyzed with these polymorphisms, the model achieved a similar prediction for dementia as the genes only model. Conclusion: These data indicate that gene–gene interactions form significant models to identify populations susceptible to dementia.